EDITORIAL: FROM REPRODUCTIVE HEALTH TO UNPREPARED HEALTH SYSTEM STRUCTURE: REMEMBERING WHY WE START THE DIGITAL HEALTH - Nuzulul Kusuma Putri (Universitas Airlangga, 2020)
The COVID-19 pandemic brought blessings in disguise to how we should run the new era of digital health. As the developing country with unsolved health problems, Indonesia needs some “forces” to reach the new era of health digitalization. This era is the time to enter the new order of healthcare services. The Volume 8 Number 1 was prepared before the pandemic started, but the articles were totally related to the ongoing disruption. We published our current edition by underlining the prospective of digital health on their respect of old-fashioned health problems in Indonesia. Three main topics were covered in this edition; how we start the digital health, what should be prepared, and what health problems should be addressed.